Medium-entropy low-dielectric microwave ceramic
By using a combination of ternary silicate and whisker composite porous silicon micropowder, combined with the preparation of modified Si3N4 powder, the problem of poor performance of existing microwave ceramic materials is solved, and ceramic materials with low dielectric constant and low dielectric loss are achieved, which improves its application performance.
Patent Information
- Application Number
- CN202510061719.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The comprehensive performance of existing microwave ceramic materials is not ideal, especially the low dielectric constant of magnesium silicate (Mg2SiO4), which limits its application.
Using a combination of ternary silicate A2SiO4 and whisker composite porous silicon powder, a medium-entropy microwave ceramic with low dielectric constant and low dielectric loss is formed by mixing equimolar elements Mg, Co, Zn and preparing modified Si3N4 powder.
It achieves excellent performance with low dielectric constant and low dielectric loss, improves the comprehensive performance of ceramic materials, and is suitable for applications such as microwave circuits.
Smart Images

Figure CN119899043A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic ceramic materials, and in particular relates to medium-entropy low-dielectric microwave ceramics. Background Art
[0002] Microwaves generally refer to electromagnetic waves with a frequency between 300MHz and 300GHz and a wavelength between 1mm and 1m. Microwave ceramic materials are used in microwave circuits to achieve the transmission, reflection and absorption of electromagnetic waves. They are widely used in the manufacture of dielectric resonators, dielectric filters, duplexers, microwave dielectric antennas and other microwave technology fields.
[0003] Among numerous microwave ceramic materials, magnesium silicate (Mg2SiO4) has received much attention in research at home and abroad. Magnesium silicate (Mg2SiO4) has a low dielectric constant, but its overall performance is not ideal, which limits its application to a certain extent. Summary of the invention
[0004] 1. Technical issues to be solved
[0005] In view of the deficiencies in the prior art, the present invention provides a medium-entropy low-dielectric microwave ceramic, which solves the problems raised in the above-mentioned background technology.
[0006] (II) Technical solution
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] A medium-entropy low-dielectric microwave ceramic, the constituent materials of which include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
[0009] The above-mentioned method for preparing the medium-entropy low-dielectric microwave ceramic comprises the following steps:
[0010] Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder;
[0011] Step 2: In 50 to 100 parts of a mixed aqueous solution, add 0.1 to 0.3 parts of citric acid and 1 to 2 parts of ethylene glycol, by weight, heat to 60 to 80° C., and stir for 0.5 to 1 hour to obtain a mixed solution C. The solutes of the mixed aqueous solution include MgCl2, CoCl2, and ZnCl2, and the concentrations of MgCl2, CoCl2, and ZnCl2 are all 0.2 to 0.3 mol / L;
[0012] Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 20 to 40 minutes, adjust the pH to 9 to 10 with sodium bicarbonate, continue stirring for 1 to 2 hours, heat to 60 to 80°C, then add 2 to 4 parts of the mixed powder obtained in step 1, stir for 10 to 20 minutes, filter, press and sinter in sequence to obtain medium-entropy low-dielectric microwave ceramics.
[0013] The method for preparing the whisker composite porous silicon powder comprises the following steps:
[0014] S1. By weight, take 10 parts of silicon powder and 0.18 to 0.22 parts of refined naphthalene, add 30 to 50 parts of ether, stir evenly, heat and evaporate to obtain a solid;
[0015] S2. In parts by weight, the solid material in S1 was mixed with 6 to 10 parts of modified Si3N4 powder to obtain a solid mixture B, 10 to 15 parts of the solid mixture B were added to 10 to 15 parts by mass fraction of 1% polyvinyl alcohol aqueous solution, and wet ball milled to obtain a mixed slurry;
[0016] S3. The mixed slurry is placed in a drying furnace for drying, forming and sintering at a sintering temperature of 1450-1550°C, cooled to room temperature, crushed, and passed through a 80-120 mesh sieve to obtain a whisker composite porous silicon powder.
[0017] Furthermore, the preparation method of the modified Si3N4 powder comprises the following steps:
[0018] Q1. By weight, 5 parts of α-Si3N4 powder are added to 40-60 parts of a 2-4% sodium polyacrylate aqueous solution, heated to 40-60°C, stirred for 10-30 minutes, and then 0.2-0.4 parts of a 30% hydrogen peroxide solution are added dropwise, stirred for 1-2 hours, and filtered to obtain a pretreated powder;
[0019] Q2. By weight, add 0.3-0.5 parts of phosphoric acid to 10-20 parts of ethanol, then add 0.4-0.6 parts of nano magnesium fluoride, and continue stirring for 5-15 minutes to obtain a modified solution;
[0020] Q3. Add the pretreated powder of Q1 to the modified liquid of Q2, stir for 1 to 2 hours, filter, put into a muffle furnace, calcine for 0.5 to 1 hour, cool to room temperature, and obtain modified Si3N4 powder.
[0021] Furthermore, the calcination temperature in Q3 is 300-400° C., and the calcination time is 0.5-1 h.
[0022] Furthermore, the sintering temperature in S3 is 1450-1550° C., and the sintering time is 1-2 hours.
[0023] Furthermore, the sintering temperature in step 3 is 1300-1500° C., and the sintering time is 2-6 hours.
[0024] Furthermore, the heating rate of the sintering temperature in step 3 is 1 to 10° C. / min.
[0025] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0026] 1. In the preparation of the modified silicon nitride powder of the present invention, the α-Si3N4 powder is surface treated by adding sodium polyacrylate to make it have a higher matching ability in terms of compatibility, and then phosphoric acid and nano magnesium fluoride are added to achieve mutual doping between inorganic powders. The addition of nano magnesium fluoride can improve the quality factor of the material, and in the subsequent process of Si3N4 whisker generation, since nano magnesium fluoride is attached to the Si3N4 grain boundary, it can inhibit the growth of grains and play a role in fixing and strengthening the grain boundary.
[0027] 2. The whisker composite porous silicon micropowder obtained by combining modified silicon nitride powder with silicon dioxide, wherein the addition of refined naphthalene makes it produce a porous structure, giving the whisker composite porous silicon micropowder a lower dielectric constant, and at the same time the porous structure provides a reaction matrix with a pore structure for silicon dioxide and metal elements, and a large amount of ternary silicate (A2SiO4) is generated in situ at the pore interface, avoiding the generation of the second phase, ensuring the dielectric properties and reaction stability of the generated ternary silicate (A2SiO4), and finally achieving the synergistic effect of the porous structure and modified silicon nitride in the solution, so that the obtained ceramic material finally has the excellent properties of low dielectric constant and low dielectric loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Attached Figure 1 This is the XRD diagram of the medium-entropy low-dielectric microwave ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] A medium-entropy low-dielectric microwave ceramic, the constituent materials of which include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
[0032] First, a modified Si3N4 powder is prepared. The preparation method of the modified Si3N4 powder comprises the following steps:
[0033] Q1. By weight, 5 parts of α-Si3N4 powder were added to 50 parts of 3% sodium polyacrylate aqueous solution, heated to 50 ° C, stirred for 20 minutes, and then 0.3 parts of 30% hydrogen peroxide solution were added dropwise at a uniform rate, stirred for 1 hour, and filtered to obtain the pretreated powder;
[0034] Q2. By weight, 0.4 parts of phosphoric acid were added to 15 parts of ethanol, and then 0.5 parts of nano-magnesium fluoride were added, and stirring was continued for 10 minutes to obtain a modified solution;
[0035] Q3. Add the pretreated powder of Q1 to the modified liquid of Q2, stir for 1.5 hours, filter, put into a muffle furnace, calcine at 350°C for 0.7 hours, cool to room temperature, and obtain modified Si3N4 powder.
[0036] Then, the whisker composite porous silicon powder is prepared, comprising the following steps:
[0037] S1. By weight, take 10 parts of silicon powder and 0.20 parts of refined naphthalene, add 40 parts of ether, stir, heat and evaporate, recover ether in the evaporator for reuse, and obtain the remaining solid;
[0038] S2. In parts by weight, the solid material in S1 was mixed with 8 parts of modified Si3N4 powder to obtain a solid mixture B, 10 parts of the solid mixture B were added to 10 parts by mass fraction of 1% polyvinyl alcohol aqueous solution, and wet ball milled to obtain a mixed slurry;
[0039] S3. The mixed slurry is placed in a drying furnace for drying, forming and sintering at a sintering temperature of 1500°C for 1 hour, cooled to room temperature, crushed, and passed through a 100-mesh sieve to obtain a whisker composite porous silicon powder.
[0040] A method for preparing medium-entropy low-dielectric microwave ceramics comprises the following steps:
[0041] Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a solid mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder;
[0042] Step 2: In 100 parts of the mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added by weight, heated to 70°C, and stirred for 0.5h to obtain a mixed solution C. The solutes of the mixed aqueous solution include MgCl2, CoCl2 and ZnCl2, and the concentrations of MgCl2, CoCl2 and ZnCl2 are all 0.25 mol / L;
[0043] Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1 hour, heat to 70°C, then add 3 parts of the mixed powder obtained in step 1, stir for 15 minutes, filter, press and sinter in sequence, and obtain medium-entropy low-dielectric microwave ceramics after sintering. The sintering process is heated to 1400°C at a rate of 5°C / min, and then kept warm for 4 hours to obtain medium-entropy low-dielectric microwave ceramics.
[0044] Example 2
[0045] A medium-entropy low-dielectric microwave ceramic, the constituent materials of which include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
[0046] First, a modified Si3N4 powder is prepared. The preparation method of the modified Si3N4 powder comprises the following steps:
[0047] Q1. By weight, 5 parts of α-Si3N4 powder were added to 40 parts of 2% sodium polyacrylate aqueous solution, heated to 40 ° C, stirred for 10 minutes, and then 0.2 parts of 30% hydrogen peroxide solution were added dropwise, stirred for 1 hour, and filtered to obtain the pretreated powder;
[0048] Q2. By weight, 0.3 parts of phosphoric acid were added to 10 parts of ethanol, and then 0.4 parts of nano-magnesium fluoride were added, and stirring was continued for 5 minutes to obtain a modified solution;
[0049] Q3. Add the pretreated powder of Q1 to the modified liquid of Q2, stir for 1 hour, filter, put into a muffle furnace, calcine at 300℃ for 0.5 hour, cool to room temperature, and obtain modified Si3N4 powder.
[0050] Then, the whisker composite porous silicon powder is prepared, comprising the following steps:
[0051] S1. By weight, take 10 parts of silicon powder and 0.18 parts of refined naphthalene, add 30 parts of ether, stir evenly, heat and evaporate, recover ether in the evaporator for reuse, and obtain the remaining solid;
[0052] S2. In parts by weight, the solid material in S1 was mixed with 6 parts of modified Si3N4 powder to obtain a solid mixture B, 10 parts of the solid mixture B were added to 10 parts by mass fraction of 1% aqueous solution of polyvinyl alcohol, and wet ball milled to obtain a mixed slurry;
[0053] S3. The mixed slurry is placed in a drying furnace for drying, forming and sintering at a sintering temperature of 1450°C for 1.5 hours, cooled to room temperature, crushed, and passed through an 80-mesh sieve to obtain a whisker composite porous silicon powder.
[0054] A method for preparing medium-entropy low-dielectric microwave ceramics comprises the following steps:
[0055] Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a solid mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder;
[0056] Step 2: In 50 parts of a mixed aqueous solution, 0.1 parts of citric acid and 1 part of ethylene glycol are added by weight, heated to 60°C, and stirred for 0.5h to obtain a mixed solution C. The solutes of the mixed aqueous solution include MgCl2, CoCl2 and ZnCl2, and the concentrations of MgCl2, CoCl2 and ZnCl2 are all 0.2 mol / L;
[0057] Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 20 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1 hour, heat to 60°C, then add 2 parts of the mixed powder obtained in step 1, stir for 10 minutes, filter, press and sinter in sequence, and obtain medium-entropy low-dielectric microwave ceramics after sintering. The sintering process is heated to 1300°C at a rate of 1°C / min, and then kept warm for 2 hours to obtain medium-entropy low-dielectric microwave ceramics.
[0058] Example 3
[0059] A medium-entropy low-dielectric microwave ceramic, the constituent materials of which include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
[0060] First, a modified Si3N4 powder is prepared. The preparation method of the modified Si3N4 powder comprises the following steps:
[0061] Q1. By weight, 5 parts of α-Si3N4 powder were added to 60 parts of a 4% sodium polyacrylate aqueous solution, heated to 60°C, stirred for 30 minutes, and then 0.4 parts of a 30% hydrogen peroxide solution were added dropwise, stirred for 2 hours, and filtered to obtain the pretreated powder;
[0062] Q2. By weight, 0.5 parts of phosphoric acid were added to 20 parts of ethanol, and then 0.6 parts of nano-magnesium fluoride were added, and stirring was continued for 15 minutes to obtain a modified solution;
[0063] Q3. Add the pretreated powder of Q1 to the modified liquid of Q2, stir for 2 hours, filter, put into a muffle furnace, calcine at 400°C for 1 hour, cool to room temperature, and obtain modified Si3N4 powder.
[0064] Then, the whisker composite porous silicon powder is prepared, comprising the following steps:
[0065] S1. By weight, take 10 parts of silicon powder and 0.22 parts of refined naphthalene, add 50 parts of ether, stir evenly, heat and evaporate, recover the ether in the evaporator for reuse, and the remaining solid is obtained;
[0066] S2. In parts by weight, the solid material in S1 was mixed with 10 parts of modified Si3N4 powder to obtain a solid mixture B, 15 parts of the solid mixture B were added to 15 parts by mass fraction of 1% polyvinyl alcohol aqueous solution, and wet ball milled to obtain a mixed slurry;
[0067] S3. The mixed slurry is placed in a drying furnace for drying, forming and sintering. The sintering temperature is 1550°C and the sintering time is 1h. The mixture is cooled to room temperature, crushed, and passed through a 120-mesh sieve to obtain a whisker composite porous silicon powder.
[0068] A method for preparing medium-entropy low-dielectric microwave ceramics comprises the following steps:
[0069] Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a solid mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder;
[0070] Step 2: In 100 parts of the mixed aqueous solution, 0.3 parts of citric acid and 2 parts of ethylene glycol are added by weight, heated to 80°C, and stirred for 1 hour to obtain a mixed solution C. The solutes of the mixed aqueous solution include MgCl2, CoCl2 and ZnCl2, and the concentrations of MgCl2, CoCl2 and ZnCl2 are all 0.3 mol / L;
[0071] Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 40 minutes, adjust the pH to 10 with sodium bicarbonate, continue stirring for 2 hours, heat to 80°C, then add 4 parts of the mixed powder obtained in step 1, stir for 20 minutes, filter, press and sinter in sequence, and obtain medium-entropy low-dielectric microwave ceramics after sintering. The sintering process is heated to 1500°C at a rate of 10°C / min, and then kept warm for 6 hours to obtain medium-entropy low-dielectric microwave ceramics.
[0072] Example 4
[0073] A medium-entropy low-dielectric microwave ceramic, the constituent materials of which include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
[0074] First, a modified Si3N4 powder is prepared. The preparation method of the modified Si3N4 powder comprises the following steps:
[0075] Q1. By weight, 5 parts of α-Si3N4 powder were added to 45 parts of 2.5% sodium polyacrylate aqueous solution, heated to 45 ° C, stirred for 15 minutes, and then 0.25 parts of 30% hydrogen peroxide solution were added dropwise, stirred for 1.2 hours, and filtered to obtain the pretreated powder;
[0076] Q2. By weight, 0.35 parts of phosphoric acid were added to 12 parts of ethanol, and then 0.45 parts of nano-magnesium fluoride were added, and stirring was continued for 8 minutes to obtain a modified solution;
[0077] Q3. Add the pretreated powder of Q1 to the modified liquid of Q2, stir for 1.2 hours, filter, put into a muffle furnace, calcine at 320°C for 0.6 hours, cool to room temperature, and obtain modified Si3N4 powder.
[0078] Then, the whisker composite porous silicon powder is prepared, comprising the following steps:
[0079] S1. By weight, take 10 parts of silicon powder and 0.19 parts of refined naphthalene, add 35 parts of ether, stir evenly, heat and evaporate, recover ether in the evaporator for reuse, and obtain the remaining solid;
[0080] S2. In parts by weight, the solid material in S1 was mixed with 7 parts of modified Si3N4 powder to obtain a solid mixture B, 11 parts of the solid mixture B were added to 12 parts by mass fraction of 1% polyvinyl alcohol aqueous solution, and wet ball milled to obtain a mixed slurry;
[0081] S3. The mixed slurry is placed in a drying furnace for drying, forming and sintering. The sintering temperature is 1480°C and the sintering time is 1h. The mixture is cooled to room temperature, crushed, and passed through a 90-mesh sieve to obtain a whisker composite porous silicon powder.
[0082] A method for preparing medium-entropy low-dielectric microwave ceramics comprises the following steps:
[0083] Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a solid mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder;
[0084] Step 2: In 60 parts of a mixed aqueous solution, 0.15 parts of citric acid and 1.2 parts of ethylene glycol were added by weight, heated to 65°C, and stirred for 0.6h to obtain a mixed solution C. The solutes of the mixed aqueous solution included MgCl2, CoCl2, and ZnCl2, and the concentrations of MgCl2, CoCl2, and ZnCl2 were all 0.23 mol / L;
[0085] Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 25 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1.2 hours, heat to 65°C, then add 2.5 parts of the mixed powder obtained in step 1, stir for 12 minutes, filter, press and sinter in sequence, and obtain medium-entropy low-dielectric microwave ceramics after sintering. The sintering process is heated to 1350°C at a rate of 4°C / min, and then kept warm for 3 hours to obtain medium-entropy low-dielectric microwave ceramics.
[0086] Example 5
[0087] A medium-entropy low-dielectric microwave ceramic, the constituent materials of which include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
[0088] First, a modified Si3N4 powder is prepared. The preparation method of the modified Si3N4 powder comprises the following steps:
[0089] Q1. By weight, 5 parts of α-Si3N4 powder were added to 55 parts of a 3.5% sodium polyacrylate aqueous solution, heated to 55 ° C, stirred for 25 minutes, and then 0.35 parts of a 30% hydrogen peroxide solution was added dropwise, stirred for 1.8 hours, and filtered to obtain a pretreated powder;
[0090] Q2. By weight, 0.45 parts of phosphoric acid were added to 18 parts of ethanol, and then 0.55 parts of nano-magnesium fluoride were added, and stirring was continued for 14 minutes to obtain a modified solution;
[0091] Q3. Add the pretreated powder of Q1 to the modified liquid of Q2, stir for 1.8 hours, filter, put into a muffle furnace, calcine at 380°C for 0.8 hours, cool to room temperature, and obtain modified Si3N4 powder.
[0092] Then, the whisker composite porous silicon powder is prepared, comprising the following steps:
[0093] S1. By weight, take 10 parts of silicon powder and 0.21 parts of refined naphthalene, add 45 parts of ether, stir evenly, heat and evaporate, recover the ether in the evaporator for reuse, and the remaining solid is obtained;
[0094] S2. In parts by weight, the solid material in S1 was mixed with 9 parts of modified Si3N4 powder to obtain a solid mixture B, 14 parts of the solid mixture B were added to 14 parts of a 1% aqueous solution of polyvinyl alcohol by mass fraction, and wet ball milled to obtain a mixed slurry;
[0095] S3. The mixed slurry is placed in a drying furnace for drying, forming and sintering. The sintering temperature is 1540°C and the sintering time is 1h. The mixture is cooled to room temperature, crushed, and passed through a 110-mesh sieve to obtain a whisker composite porous silicon powder.
[0096] A method for preparing medium-entropy low-dielectric microwave ceramics comprises the following steps:
[0097] Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a solid mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder;
[0098] Step 2: In 80 parts of a mixed aqueous solution, 0.25 parts of citric acid and 1.8 parts of ethylene glycol were added by weight, heated to 75°C, and stirred for 0.9h to obtain a mixed solution C. The solutes of the mixed aqueous solution included MgCl2, CoCl2, and ZnCl2, and the concentrations of MgCl2, CoCl2, and ZnCl2 were all 0.28 mol / L.
[0099] Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 35 minutes, adjust the pH to 10 with sodium bicarbonate, continue stirring for 1.8 hours, heat to 75°C, then add 3.5 parts of the mixed powder obtained in step 1, stir for 18 minutes, filter, press and sinter in sequence, and obtain medium-entropy low-dielectric microwave ceramics after sintering. The sintering process is heated to 1450°C at a rate of 9°C / min, and then kept warm for 5.5 hours to obtain medium-entropy low-dielectric microwave ceramics.
[0100] Comparative Example 1
[0101] Different from Example 1, in the preparation of medium-entropy low-dielectric microwave ceramics, the modified Si3N4 powder is replaced by the pretreated powder dry material prepared in this comparative example.
[0102] A medium-entropy low-dielectric microwave ceramic, the constituent materials of which include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
[0103] First, a pre-treated powder dry product is prepared. The preparation method of the pre-treated powder dry product comprises the following steps:
[0104] Q1. By weight, 5 parts of α-Si3N4 powder were added to 50 parts of 3% sodium polyacrylate aqueous solution, heated to 50 ° C, stirred for 20 minutes, and then 0.3 parts of 30% hydrogen peroxide solution were added dropwise at a uniform rate, stirred for 1 hour, and filtered to obtain the pretreated powder;
[0105] Q2. Place the pretreated powder prepared in Q1 into a muffle furnace, calcine at 350°C for 0.7h, cool to room temperature, and obtain the pretreated powder dry product.
[0106] Then, the whisker composite porous silicon powder is prepared, comprising the following steps:
[0107] S1. By weight, take 10 parts of silicon powder and 0.20 parts of refined naphthalene, add 40 parts of ether, stir, heat and evaporate, recover ether in the evaporator for reuse, and obtain the remaining solid;
[0108] S2. In parts by weight, the solid material in S1 was mixed with 8 parts of the pretreated powder dried material to obtain a solid mixture B, 10 parts of the solid mixture B were added to 10 parts by mass fraction of 1% aqueous solution of polyvinyl alcohol, and wet ball milled to obtain a mixed slurry;
[0109] S3. The mixed slurry is placed in a drying furnace for drying, forming and sintering at a sintering temperature of 1500°C for 1 hour, cooled to room temperature, crushed, and passed through a 100-mesh sieve to obtain a whisker composite porous silicon powder.
[0110] A method for preparing medium-entropy low-dielectric microwave ceramics comprises the following steps:
[0111] Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a solid mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder;
[0112] Step 2: In 100 parts of the mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added by weight, heated to 70°C, and stirred for 0.5h to obtain a mixed solution C. The solutes of the mixed aqueous solution include MgCl2, CoCl2 and ZnCl2, and the concentrations of MgCl2, CoCl2 and ZnCl2 are all 0.25 mol / L;
[0113] Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1 hour, heat to 70°C, then add 3 parts of the mixed powder obtained in step 1, stir for 15 minutes, filter, press and sinter in sequence, and obtain medium-entropy low-dielectric microwave ceramics after sintering. The sintering process is heated to 1400°C at a rate of 5°C / min, and then kept warm for 4 hours to obtain medium-entropy low-dielectric microwave ceramics.
[0114] Comparative Example 2
[0115] Different from Example 1, in the preparation method of whisker composite porous silicon powder, refined naphthalene is not added.
[0116] A medium-entropy low-dielectric microwave ceramic, the constituent materials of which include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
[0117] First, a modified Si3N4 powder is prepared. The preparation method of the modified Si3N4 powder comprises the following steps:
[0118] Q1. By weight, 5 parts of α-Si3N4 powder were added to 50 parts of 3% sodium polyacrylate aqueous solution, heated to 50 ° C, stirred for 20 minutes, and then 0.3 parts of 30% hydrogen peroxide solution were added dropwise at a uniform rate, stirred for 1 hour, and filtered to obtain the pretreated powder;
[0119] Q2. By weight, 0.4 parts of phosphoric acid were added to 15 parts of ethanol, and then 0.5 parts of nano-magnesium fluoride were added, and stirring was continued for 10 minutes to obtain a modified solution;
[0120] Q3. Add the pretreated powder of Q1 to the modified liquid of Q2, stir for 1.5 hours, filter, put into a muffle furnace, calcine at 350°C for 0.7 hours, cool to room temperature, and obtain modified Si3N4 powder.
[0121] Then, the whisker composite porous silicon powder is prepared, comprising the following steps:
[0122] S1. In parts by weight, 10 parts of silicon powder were added to 40 parts of ether, stirred, and then heated and evaporated, and the ether was recovered and reused in the evaporator to obtain a solid;
[0123] S2. In parts by weight, the solid material in S1 was mixed with 8 parts of modified Si3N4 powder to obtain a solid mixture B, 10 parts of the solid mixture B were added to 10 parts by mass fraction of 1% polyvinyl alcohol aqueous solution, and wet ball milled to obtain a mixed slurry;
[0124] S3. The mixed slurry is placed in a drying furnace for drying, forming and sintering at a sintering temperature of 1500°C for 1 hour, cooled to room temperature, crushed, and passed through a 100-mesh sieve to obtain a whisker composite porous silicon powder.
[0125] A method for preparing medium-entropy low-dielectric microwave ceramics comprises the following steps:
[0126] Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a solid mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder;
[0127] Step 2: In 100 parts of the mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added by weight, heated to 70°C, and stirred for 0.5h to obtain a mixed solution C. The solutes of the mixed aqueous solution include MgCl2, CoCl2 and ZnCl2, and the concentrations of MgCl2, CoCl2 and ZnCl2 are all 0.25 mol / L;
[0128] Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1 hour, heat to 70°C, then add 3 parts of the mixed powder obtained in step 1, stir for 15 minutes, filter, press and sinter in sequence, and obtain medium-entropy low-dielectric microwave ceramics after sintering. The sintering process is heated to 1400°C at a rate of 5°C / min, and then kept warm for 4 hours to obtain medium-entropy low-dielectric microwave ceramics.
[0129] Comparative Example 3
[0130] Different from Example 1, in the preparation of medium-entropy low-dielectric microwave ceramics, the modified Si3N4 powder is replaced by a pretreated powder dry product, and refined naphthalene is not added in the preparation method of the whisker composite porous silicon powder.
[0131] A medium-entropy low-dielectric microwave ceramic, the constituent materials of which include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
[0132] First, a pre-treated powder dry product is prepared. The preparation method of the pre-treated powder dry product comprises the following steps:
[0133] Q1. By weight, 5 parts of α-Si3N4 powder were added to 50 parts of 3% sodium polyacrylate aqueous solution, heated to 50 ° C, stirred for 20 minutes, and then 0.3 parts of 30% hydrogen peroxide solution were added dropwise at a uniform rate, stirred for 1 hour, and filtered to obtain the pretreated powder;
[0134] Q2. Place the pretreated powder prepared in Q1 into a muffle furnace, calcine at 350°C for 0.7h, cool to room temperature, and obtain the pretreated powder dry product.
[0135] Then, the whisker composite porous silicon powder is prepared, comprising the following steps:
[0136] S1. By weight, 10 parts of silicon powder were added to 40 parts of ether, stirred evenly, heated and evaporated, and the ether was recovered and reused in the evaporator to obtain a solid;
[0137] S2. In parts by weight, the solid material in S1 was mixed with 8 parts of the pretreated powder dried material to obtain a solid mixture B, 10 parts of the solid mixture B were added to 10 parts by mass fraction of 1% aqueous solution of polyvinyl alcohol, and wet ball milled to obtain a mixed slurry;
[0138] S3. The mixed slurry is placed in a drying furnace for drying, forming and sintering at a sintering temperature of 1500°C for 1 hour, cooled to room temperature, crushed, and passed through a 100-mesh sieve to obtain a whisker composite porous silicon powder.
[0139] A method for preparing medium-entropy low-dielectric microwave ceramics comprises the following steps:
[0140] Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a solid mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder;
[0141] Step 2: In 100 parts of the mixed aqueous solution, 0.2 parts of citric acid and 1.5 parts of ethylene glycol are added by weight, heated to 70°C, and stirred for 0.5h to obtain a mixed solution C. The solutes of the mixed aqueous solution include MgCl2, CoCl2 and ZnCl2, and the concentrations of MgCl2, CoCl2 and ZnCl2 are all 0.25 mol / L;
[0142] Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 30 minutes, adjust the pH to 9 with sodium bicarbonate, continue stirring for 1 hour, heat to 70°C, then add 3 parts of the mixed powder obtained in step 1, stir for 15 minutes, filter, press and sinter in sequence, and obtain medium-entropy low-dielectric microwave ceramics after sintering. The sintering process is heated to 1400°C at a rate of 5°C / min, and then kept warm for 4 hours to obtain medium-entropy low-dielectric microwave ceramics.
[0143] The medium entropy low dielectric microwave ceramics prepared in the embodiments of the present invention and the comparative examples were used as samples, and the relative dielectric constant ε of the samples was tested using the Hakki-Collemon dielectric resonant cavity method and the Agilent 8753ES 40 GHz vector network analyzer. r And quality factor Q×f, the temperature coefficient of the sample was tested by the temperature box method, and the results are shown in Table 1.
[0144]
[0145] Table 1
[0146] From the data in Table 1 and Examples 1 to 5, it can be seen that the dielectric constants of the medium entropy microwave ceramics prepared by the present invention are all between 6.9 and 7.3, and the quality factors are all greater than 1.1×10 5 , with excellent loss performance and temperature coefficients of -10±3, proving that the medium-entropy low-dielectric microwave ceramics prepared by the present invention have excellent comprehensive properties.
[0147] Combining the contents of Comparative Example 1 and Example 1 and the corresponding data in Table 1, it can be seen that the dielectric constant of the medium-entropy low-dielectric microwave ceramic prepared in Comparative Example 1 is 7.46, which is significantly greater than the dielectric constant of the medium-entropy microwave ceramic prepared in Example 1, and the loss is significantly increased; at the same time, the quality factor is less than the quality factor of Example 1, and the temperature coefficient is reduced to -16ppm / ℃. It shows that the addition of nano-magnesium fluoride and phosphoric acid can improve the comprehensive performance of the prepared medium-entropy low-dielectric microwave ceramic.
[0148] In Comparative Example 2, refined naphthalene was not added, and the dielectric constant of the prepared medium-entropy low-dielectric microwave ceramic was also significantly higher than 6.94, which was 8.12, and the quality factor was reduced to 100700. The loss of the medium-entropy low-dielectric microwave ceramic became larger, and the temperature coefficient was reduced, which proved that its energy storage performance was unstable. Overall, the overall performance of the medium-entropy low-dielectric microwave ceramic prepared in Comparative Example 2 was reduced. Compared with Example 1, it is proved that the addition of refined naphthalene can improve the overall performance of the prepared medium-entropy low-dielectric microwave ceramic.
[0149] Comparative Example 3 is based on Comparative Example 1, but refined naphthalene is not added in the preparation of the whisker composite porous silicon powder. The dielectric constant of the prepared medium-entropy low-dielectric microwave ceramic is higher than that of Comparative Example 1 and Comparative Example 2, the quality factor is lower than that of Comparative Example 1 and Comparative Example 2, and the temperature coefficient is also reduced. This shows that the modified Si3N4 prepared by adding phosphoric acid and nano-magnesium fluoride can produce a synergistic effect with the introduction of refined naphthalene, and synergistically improve the performance of the prepared whisker composite porous silicon powder, thereby improving the overall performance of the prepared medium-entropy low-dielectric microwave ceramic.
[0150] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A medium entropy low dielectric microwave ceramic, characterized in that: Its constituent materials include ternary silicate A2SiO4 and whisker composite porous silicon powder, wherein A is composed of equimolar elements Mg, Co and Zn.
2. The medium-entropy low-dielectric microwave ceramic according to claim 1, characterized in that: The method for preparing the medium-entropy low-dielectric microwave ceramic comprises the following steps: Step 1: Mix MgO, CoO and ZnO powders in an equal molar ratio to obtain a mixture Z, grind the mixture Z in a ball mill using deionized water as a grinding medium by wet grinding to a particle size of less than 10 microns, and dry to obtain a mixed powder; Step 2: In 50 to 100 parts of a mixed aqueous solution, add 0.1 to 0.3 parts of citric acid and 1 to 2 parts of ethylene glycol, by weight, heat to 60 to 80° C., and stir for 0.5 to 1 hour to obtain a mixed solution C. The solutes of the mixed aqueous solution include MgCl2, CoCl2, and ZnCl2, and the concentrations of MgCl2, CoCl2, and ZnCl2 are all 0.2 to 0.3 mol / L; Step 3: Weigh 5 parts of whisker composite porous silicon powder by weight, add it to the mixed solution C of step 2, stir for 20 to 40 minutes, adjust the pH to 9 to 10 with sodium bicarbonate, continue stirring for 1 to 2 hours, heat to 60 to 80°C, then add 2 to 4 parts of the mixed powder obtained in step 1, stir for 10 to 20 minutes, filter, press and sinter in sequence to obtain medium-entropy low-dielectric microwave ceramics.
3. The medium-entropy low-dielectric microwave ceramic according to claim 2, characterized in that: The method for preparing the whisker composite porous silicon powder comprises the following steps: S1. By weight, take 10 parts of silicon powder and 0.18 to 0.22 parts of refined naphthalene, add 30 to 50 parts of ether, stir evenly, heat and evaporate to obtain a solid; S2. In parts by weight, the solid material in S1 was mixed with 6 to 10 parts of modified Si3N4 powder to obtain a solid mixture B, 10 to 15 parts of the solid mixture B were added to 10 to 15 parts by mass fraction of 1% polyvinyl alcohol aqueous solution, and wet ball milled to obtain a mixed slurry; S3. The mixed slurry in S2 is placed in a drying furnace for drying, forming and sintering, then cooled to room temperature, crushed, and passed through a 80-120 mesh sieve to obtain whisker composite porous silicon powder.
4. The medium-entropy low-dielectric microwave ceramic according to claim 3, characterized in that: The preparation method of the modified Si3N4 powder comprises the following steps: Q1. By weight, 5 parts of α-Si3N4 powder are added to 40-60 parts of a 2-4% sodium polyacrylate aqueous solution, heated to 40-60°C, stirred for 10-30 minutes, and then 0.2-0.4 parts of a 30% hydrogen peroxide solution are added dropwise, stirred for 1-2 hours, and filtered to obtain a pretreated powder; Q2. By weight, add 0.3-0.5 parts of phosphoric acid to 10-20 parts of ethanol, then add 0.4-0.6 parts of nano magnesium fluoride, and continue stirring for 5-15 minutes to obtain a modified solution; Q3. Add the pretreated powder of Q1 to the modified liquid of Q2, stir for 1 to 2 hours, filter, put into a muffle furnace, calcine, cool to room temperature, and obtain modified Si3N4 powder.
5. The medium-entropy low-dielectric microwave ceramic according to claim 4, characterized in that: The calcination temperature in Q3 is 300-400° C., and the calcination time is 0.5-1 h.
6. The medium-entropy low-dielectric microwave ceramic according to claim 3, characterized in that: The sintering temperature in S3 is 1450-1550° C., and the sintering time is 1-2 hours.
7. The medium-entropy low-dielectric microwave ceramic according to claim 2, characterized in that: The sintering temperature in step 3 is 1300-1500° C., and the sintering time is 2-6 hours.
8. The medium-entropy low-dielectric microwave ceramic according to claim 2, characterized in that: The heating rate of the sintering temperature in step 3 is 1 to 10° C. / min.
Citation Information
Patent Citations
Zn-contained high-strength aluminum-based lightweight medium-entropy alloy and preparation method thereof
CN110106407A
Medium-entropy microwave dielectric ceramic with garnet structure and preparation method of medium-entropy microwave dielectric ceramic
CN118771855A
High-entropy metal oxide catalyst as well as preparation method and application thereof
CN118807756A
Preparation method of low permittivity nanometer microwave medium ceramic powder
CN1736951A
Ceramic composites and methods of making and using the same
US20220119316A1